2015
DOI: 10.3389/fphy.2015.00050
|View full text |Cite
|
Sign up to set email alerts
|

Simulating anomalous dispersion in porous media using the unstructured lattice Boltzmann method

Abstract: Flow in porous media is a significant challenge to many computational fluid dynamics methods because of the complex boundaries separating pore fluid and host medium. However, the rapid development of the lattice Boltzmann methods and experimental imaging techniques now allow us to efficiently and robustly simulate flows in the pore space of porous rocks. Here we study the flow and dispersion in the pore space of limestone samples using the unstructured, characteristic based off-lattice Boltzmann method. We use… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1
1

Relationship

3
5

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 32 publications
0
8
0
Order By: Relevance
“…The validity and grid convergence is This work establishes a promising venue for simulations of multiphase flows in non-trivial geometries such as real porous media, e.g., by invoking the boundary treatment developed in [18,25].…”
Section: Resultsmentioning
confidence: 93%
“…The validity and grid convergence is This work establishes a promising venue for simulations of multiphase flows in non-trivial geometries such as real porous media, e.g., by invoking the boundary treatment developed in [18,25].…”
Section: Resultsmentioning
confidence: 93%
“…Cushman and O'Malley (2015) stated that "…the occurrence of Fickian dispersion in geophysical settings is a rare event and consequently should be labeled as anomalous." Misztal et al (2015) simulated anomalous dispersion in porous media using the unstructured lattice Boltzmann method. Ruspini et al (2014) reported the results of experiments demonstrating two-phase flow instabilities.…”
Section: Introductionmentioning
confidence: 99%
“…Scientists have studied the morphology and dynamics of porous media flows and proposed a set of numerical schemes able to reproduce the observed macroscopic patterns [2,3,5,7,10,[45][46][47][48][49][50][51][52] and relevant pore-scale mechanisms [6,9,26,27,47,[53][54][55]. These studies have led to a deeper understanding of the pore-scale forces that are ultimately responsible for the macroscopic flow properties and finally to the possible upscaling of the results [6,8,48].…”
Section: Introductionmentioning
confidence: 99%